2006
DOI: 10.1017/s0266467406003282
|View full text |Cite
|
Sign up to set email alerts
|

Species–habitat associations in a Sri Lankan dipterocarp forest

Abstract: Forest structure and species distribution patterns were examined among eight topographically defined habitats for the 205 species with stems > 1 cm dbh inhabiting a 2 5-ha plot in the Sinharaja rain forest, Sri Lanka. The habitats were steep spurs, less-steep spurs, steep gullies and less-steep gullies, all at either lower or upper elevations. Mean stem density was significantly greater on the upper spurs than in the lower, less-steep gullies. Stem density was also higher on spurs than in gullies within each e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
148
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(164 citation statements)
references
References 42 publications
11
148
3
1
Order By: Relevance
“…However, the results of a homogeneous null model showed that the diversity in the two tropical forests is strongly structured by habitat association (SI Fig. 8), a mechanism not yet included in neutral theory (23,29). This result is in accordance with a recent study (36) that found that Ϸ30% of the species at BCI showed significant affinities to soil nutrient distributions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the results of a homogeneous null model showed that the diversity in the two tropical forests is strongly structured by habitat association (SI Fig. 8), a mechanism not yet included in neutral theory (23,29). This result is in accordance with a recent study (36) that found that Ϸ30% of the species at BCI showed significant affinities to soil nutrient distributions.…”
Section: Discussionsupporting
confidence: 88%
“…The effect of dispersion is important for interpreting and understanding ISAR but can be diagnosed by comparing local densities of the stems of the target species with that of all species in neighborhoods around the stems of the target species [see supporting information (SI) Table 1]. A species may appear to be a diversity accumulator or repeller through habitat association if diversity differs at different habitats [e.g., upper and lower elevation habitats at Sinharaja (23)]. This effect is analogous to the problem of heterogeneous patterns in point-pattern analysis (21,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships between forest structure and physical environments defined by topography and edaphic factors have not been determined at Yasuni, although soil type and topography may influence disturbance regimes and canopy structure in tropical lowland forests elsewhere (e.g. Gunatilleke et al 2006). The contributions of these interactions to habitat partitioning of Yasuni Myristiaceae awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of edaphic factors in maintaining local diversity has long been recognized (29,30), a thorough, quantitative assessment of the importance of soil resources on tropical tree distributions for entire communities has not been undertaken. Typically, studies have either focused on a small fraction of the tree species in any community (31-33) or related community-wide tree species distributions to topographical variables whose relationships with underlying soil resources are unknown (28,34,35). To test relationships between species distributions and soil resource availability, soil resources and species distributions need to be mapped at high spatial resolution for entire communities in plots large enough to span substantial spatial heterogeneity in soil factors.…”
mentioning
confidence: 99%